What Determines Indigenous Peoples’ Mental Health Awareness? A Descriptive Cross-Sectional Study From Nawalpur District (Quest Journal of Management and Social Sciences, 2021)
Background: The health status of indigenous people including Tharu is very poor. Despite several studies on indigenous communities, no previous studies were found about mental illness and its awareness among the Tharu people in Nepal.Objectives: This study aims to find out the awareness of mental illness among adults of the Tharu community. Within the objective the present study specific to identify the level of awareness on mental illness and to identify an association between selected socio-demographic characteristics and level of awareness on mental illness.Method: The study was based on the descriptive cross-sectional design and was conducted in 3, 4, 6, 8, and 15 wards of the Madhyabindu municipality of Nawalpur District as the majority of the Tharu's household are located in these wards. This research administered a structured questionnaire to assess awareness of Tharu adults on mental illness. Data were collected in September and October 2018. The collected data were analyzed by using descriptive statistical methods where the researcher calculated mean, standard deviation, percentage, and frequency. Chi-square test was used for inferential statistics.Result: Our analysis revealed that the socioeconomic status of the Tharu community is based on agriculture. The overall level of awareness of respondents, 35.5 % had adequate awareness of mental illness whereas 34 % had moderate awareness and 30.5 % respondents had inadequate awareness of the mental illness. The level of awareness of mental illness is statistically significant with the age of respondents, gender, marital status, education status, and occupation status.Conclusion: Based on the findings of the study, it concluded that nearly one-third of Tharu adults have an adequate level of awareness regarding mental illness. Further, the awareness level of Tharu adults tends to vary according to age, sex, education, occupation, and marital status.Implication: The findings of this study imply that mental awareness among the indigenous community is still low and the findings of the study could be used by a mental health organization to plan and implement mental health-related awareness programs in an indigenous community.